Strategi Pemeritah Dalam Menurunkan Angka Stanting di Pagesangan Barat - Yulaiha, St; Zitri, Ilham (Magister Administrasi Publik FISIP Universitas Mulawarman, 2025)
Abstract: The prevalence of stunting in Indonesia is still relatively high, namely 24.4 percent, still above the standard accepted by WHO, namely below 20 percent. This is because young women before marriage have high rates of anemia and malnutrition, which causes stunted growth of children during pregnancy. Growth retardation refers to impaired growth and development that occurs primarily in the first 1,000 days of life due to prolonged nutritional deficiencies, recurrent infections, or inadequate psychosocial stimulation. Meanwhile, in the long term, cognitive and learning abilities decrease, immunity decreases, and the risk of developing chronic diseases increases. The stunting rate in West Pagsangan is the highest in Mataram City and is considered the highest stunting rate. The aim of this research is to determine the government's strategy for reducing stunting rates in West Pagesangan. The data collection techniques used in this research used interviews, field observations and documentation. The theory used is strategic theory in his book Sedarmayanti (2014) which consists of three indicators, namely planning, involvement of top leadership, and long-term organizational programs. The results of the study show that the government's strategy for overcoming stunting in West Page Sanan Regency is good, and data available at the Page Sanan Regency Health Center shows that the stunting rate is decreasing every year. Second, the involvement of leaders as interdisciplinary actors in this case sub-district and even sub-district governments needs further improvement.